Duta Bahasa in Language Mixing: The Perspective of an Indonesian Youth Community in North Sumatra - Patrial Olivert Zega; Namiratusshofa Siregar; Alemina Br.Perangin-Angin; Aprilza Aswani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This descriptive qualitative research investigates the code-mixing phenomenon studied in the caption uploaded by the Duta Bahasa (DS) of North Sumatera on Instagram. The data source involved the last 3 batches of DS starting from 2019 to 2021. There are, 200 posts were found during their tenure as DS. The results of data analysis showed that DS of North Sumatra is not so dominant in mixing languages in their Instagram uploads. Yet, there were three types of code-mixing found, intra-sential, intra-lexical code mixing, and involving a change of pronunciation. Meanwhile, the variation of code mixing found were in several form of language-mixtures covered the foreign language-Indonesian or vice versa and local language-Indonesian. As the reason why code-mixing is used, the unavailability of the word in Indonesian and the use for translating function are the main reason in mixing language. Regarding the perspective on code-mixing, the interview indicated that DS of North Sumatera were both linguistic purism and socio-historical cognitivism.